心肺运动试验在肺癌手术风险评估中的应用 (Zhongguo Fei Ai Za Zhi, 2011)
Cardiopulmonary exercise testing (CPET) has become an important clinical tool to evaluate exercise capacity and predict outcome for patients with lung cancer being considered for lung resection. CPET can help in stratifying the surgical risk and identify those high-risk patients with lung resection. Preoperative screening using CPET allow the selection of appropriate therapeutic approach to decrease surgical complications and mortality.